WAYS TO LEARN ENGLISH - Berdiyeva Zamona (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This article provides information on modern methods of learning English. In recent years, the issue of using new information technologies in educational institutions has been increasingly raised.